Pendekatan Etnopedagogi dalam Proses Pembelajaran untuk Membentuk Karakter Peserta Didik Sekolah Dasar - Edi Rohyadi; Cindy Desiana; Ila Rosmilawati (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This study aims to describe character education implemented through an ethnopedagogical approach integrated in the learning process in elementary schools in order to shape and improve the character of students. The ethnopedagogical approach implemented at Banjar Agung 2 State Elementary School is implemented in grade 6 with Indonesian language content. The activities are divided into 3 learning phases, namely the initial activities, core activities and final activities. Ethnopedagogy in this study focuses on the local wisdom of the people of Serang City. The method used in this research is descriptive with a qualitative approach, the data is collected using observation techniques, interviews, field notes and documentation. The result is that learning by using ethnopedagogical approach is proven to be able to form and improve the character of students, namely religious, nationalist, mutual cooperation, integrity, and independent characters. The results of the discussion in this study show that the ethnopedagogical approach is open to be applied at different grade levels and subject content, depending on the level of creativity and innovation of a teacher.